K‐t accelerated aortic 4D flow MRI in under two minutes: Feasibility and impact of resolution, k‐space sampling patterns, and respiratory navigator gating on hemodynamic measurements. Issue 1 (7th March 2017) - Bollache, Emilie; Barker, Alex J; Dolan, Ryan Scott; Carr, James C; van Ooij, Pim; Ahmadian, Rouzbeh; Powell, Alex; Collins, Jeremy D; Geiger, Julia; Markl, Michael
Abstract : Purpose: To assess the performance of highly accelerated free‐breathing aortic four‐dimensional (4D) flow MRI acquired in under 2 minutes compared to conventional respiratory gated 4D flow. Methods: Eight k‐t accelerated nongated 4D flow MRI (parallel MRI with extended and averaged generalized autocalibrating partially parallel acquisition kernels [PEAK GRAPPA], R = 5, TRes = 67.2 ms) using four ky ‐kz Cartesian sampling patterns (linear, center‐out, out‐center‐out, random) and two spatial resolutions (SRes1 = 3.5 × 2.3 × 2.6 mm 3, SRes2 = 4.5 × 2.3 × 2.6 mm 3 ) were compared in vitro (aortic coarctation flow phantom) and in 10 healthy volunteers, to conventional 4D flow (16 mm‐navigator acceptance window; R = 2; TRes = 39.2 ms; SRes = 3.2 × 2.3 × 2.4 mm 3 ). The best k‐t accelerated approach was further assessed in 10 patients with aortic disease. Results: The k‐t accelerated in vitro aortic peak flow (Qmax), net flow (Qnet), and peak velocity (Vmax) were lower than conventional 4D flow indices by ≤4.7%,  ≤ 11%, and ≤22%, respectively. In vivo k‐t accelerated acquisitions were significantly shorter but showed a trend to lower image quality compared to conventional 4D flow. Hemodynamic indices for linear and out‐center‐out k‐space samplings were in agreement with conventional 4D flow (Qmax ≤ 13%, Qnet ≤ 13%, Vmax ≤ 17%, P  > 0.05). Conclusion: Aortic 4D flow MRI in under 2 minutes is feasible with moderate underestimation of flow indices. Differences in k‐space sampling patterns suggest an opportunity to mitigate image artifacts by an optimal trade‐off between scan time, acceleration, and k‐space sampling. Magn Reson Med 79:195–207, 2018. © 2018 International Society for Magnetic Resonance in Medicine.